Statistical Packages for Social Sciences workshop (SPSS) - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Chin, Mei Lee; Norhayati, Nordin; Siti Aisah, Harun; Nenie Zuryati, Abdullah; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras (Penerbit Universiti Malaysia Pahang, 2011)
The Faculty of Science & Technology Industry (FIST) conducted a half-day SPSS workshop April 20th at UMP Gam bang. The workshop was faci litated by Mr. Zulkhibri lsmaii@Mustofa and assisted by Madam Noryanti Muhammad and Miss Nor Hafizah Moslim.